A participatory stakeholder process for evaluating sustainable energy transition scenarios. (April 2020) - Höfer, Tim; Madlener, Reinhard
Abstract: This paper presents an evaluation of four energy transition scenarios under consideration of multiple stakeholder opinions. We construct a multi-criteria group decision model that applies Value-Focused Thinking to construct a holistic objective system and uses Multi-Attribute Utility Theory to evaluate the energy transition scenarios. Although the individual scenario evaluations show that the opinions of the stakeholders towards a sustainable energy transition differ largely, we are able to identify three main strands of opinions among the considered stakeholders. By bundling the stakeholder interests by employing a k-means clustering technique, we derive detailed policy recommendations for a sustainable energy transition. For the case of Germany, these are to reduce GHG and pollutant emissions and at the same time enable citizens' participation, limit the visual impact on landscapes, and ensuring internationally comparable energy-related political frameworks for the economy. For the case of a sustainable energy transition in Germany, we find that the stakeholders considered prefer either the highly ambitious Climate Protection scenario (Scenario B) or the Pan-European scenario (Scenario C). The main novelties of the study are that stakeholders are included in every step of the decision-making process and that very comprehensive energy transition scenarios, comprising the electricity, transport, heat, and industry sectors, are considered. Highlights: Energy transition policy is guided by a participatory expert stakeholder process. The analysis is based on Value-Focused Thinking, MAUT and a clustering technique. Stakeholder opinions differ widely but bundling yields core policy recommendations. Stakeholders dislike the scenario used by the German transmission system operators. High climate protection and pan-European cooperation are the more popular scenarios.